Instagram Content Analysis of #BanggaIlustratorLokal Campaign on Building the Brand Image of Sovlo - Happy Angela; Chika Dhamma Saputri; Gabriella Angelica (Jurnal Mutakallimin : Jurnal Ilmu Komunikasi, 2024)
A local brand called Sovlo collaborates with local illustrators to create illustrated fashion products, such as bags and t-shirts. In order to support Indonesian illustrators, Sovlo started a campaign called #BanggaIlustratorLokal, which is carried out both offline and online on Instagram since 2021. As it is known, content is crucial to the success of any social media campaign because everything shared on social media, including photos, videos, captions, comments, etc., contributes to how people think about a brand and eventually shapes the brand image. Therefore, as a brand, Sovlo needs to develop good content to create a positive brand image. The purpose of this study is to see how Sovlo’s brand image is shaped by the Instagram content of the #BanggaIlustratorLokal. This study is a qualitative descriptive study that uses the concepts of good social media content characteristics which are educative, entertaining, persuasive, telling a story, sharing, and finding. According to the findings of this study, Sovlo’s brand image has developed as a brand that empowers and supports Indonesian illustrators as a result of the #BanggaIlustratorLokal campaign’s use of phrases associated with local illustrators, products made in collaboration with local illustrators, and/or mention of local illustrators in the visual and/or caption.